Recommendations for the management of COVID-19 pandemic in long-term care facilities - Gosch, M.; Lim, S.; Singler, Katrin; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2021)
Long-term care facilities (LTCF) and their vulnerable residents are particularly affected by the coronavirus disease 2019 (COVID-19) pandemic. Estimates from various countries suggest that 3-66% of all COVID-19 deaths were residents of LTCF, of which 80% died in their facilities. Despite these significant numbers, recommendations for LTCF for the prevention and medical care of residents during the COVID-19 pandemic are still lacking. These recommendations are based on the existing literature and the expertise of the authors who are specialists in geriatric medicine. The recommendations are addressed to LTCF management, their operators, physicians working in LTCFs and also politicians, to provide the necessary framework conditions. We are confident that our recommendations will offer important help and guidance for LTCFs as well as their physicians. Adherence to these recommendations is likely to improve the outcomes and care of residents in long-term facilities during the COVID-19 pandemic.
CRIS-Team WoS Importer:2021-01-29